2016
DOI: 10.18632/oncotarget.13430
|View full text |Cite
|
Sign up to set email alerts
|

Chrysophanic acid reduces testosterone-induced benign prostatic hyperplasia in rats by suppressing 5α-reductase and extracellular signal-regulated kinase

Abstract: Benign prostatic hyperplasia (BPH) is one of the most common chronic diseases in male population, of which incidence increases gradually with age. In this study, we investigated the effect of chrysophanic acid (CA) on BPH. BPH was induced by a 4-week injection of testosterone propionate (TP). Four weeks of further injection with vehicle, TP, TP + CA, TP + finasteride was carried on. In the CA treatment group, the prostate weight was reduced and the TP-induced histological changes were restored as the normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Immunohistochemical analysis was performed as previously described (31). Antibodies for translocase of the outer membrane subunit 20 (TOM20) and UCP1, -2, and -3 were purchased from Santa Cruz Biotechnology.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Immunohistochemical analysis was performed as previously described (31). Antibodies for translocase of the outer membrane subunit 20 (TOM20) and UCP1, -2, and -3 were purchased from Santa Cruz Biotechnology.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Male SD rats 5 mg/kg In vivo [99] anthraquinone were not significantly different. However, in the CCl 4 -induced liver injury mice, the C max and AUC 0~∞ were significantly increased.…”
Section: Mouse Osteoblast Unknownmentioning
confidence: 81%
“…Next, we established a vitro model for BPH using normal prostate epithelial RWPE-1 cells for further studies. Results from our previous report showed that TP treatment induced the proliferation of RWPE-1 cells [ 39 ]. To find the most effective concentration of TP, we treated the RWPE-1 cells with various concentrations of TP and evaluated the changes.…”
Section: Resultsmentioning
confidence: 99%